RELATIONSHIP BETWEEN EXCLUSIVE BREASTFEEDING AND INFANT WEIGHT GAIN AT AGE 0-6 MONTHS - Syariena Syariena; Asima Lamtiar Hotnauli Pakpahan; Elpriska Elpriska (Universitas Bina Bangsa Getsempena, 2025)
The growth of infant body weight from 0 to 6 months of age is a key indicator for assessing nutritional adequacy and overall health in early life. Exclusive breastfeeding, as recommended by the World Health Organization (WHO), is believed to fully meet infants' nutritional needs and provide immunological protection. This study aims to determine the relationship between exclusive breastfeeding and infant weight gain at the Posyandu in Danau Usung Village. The study used a correlational analytic design with a cross-sectional approach, involving 50 infants selected through purposive sampling. Data were collected through interviews, observations, and weight measurements. The results showed that among the 30 infants who received exclusive breastfeeding, 93.3% had normal body weight, while in the group of infants who did not receive exclusive breastfeeding, only 75% had normal body weight. Statistical analysis yielded a p-value of 0.013 (p < 0.05), indicating a significant relationship between exclusive breastfeeding and infant weight gain.These findings affirm the important role of exclusive breastfeeding in supporting optimal nutritional status and growth in infants. In addition to providing complete nutrition, breast milk also protects infants from infections and digestive disorders, contributing to weight gain consistent with the WHO growth curve. The results of this study are expected to serve as a foundation for enhancing maternal education regarding the importance of exclusive breastfeeding during the first six months of a baby’s life.